CMET-06. DISTANT BRAIN FAILURE AND SALVAGE FREE SURVIVAL FOR RADIOSURGERY-TREATED MELANOMA BRAIN METASTASES IN THE ERA OF CHECKPOINT INHIBITOR IMMUNOTHERAPY. (5th November 2018) - Nguyen, Steven; Keller, Andrew; Pearson, Luke; All, Sean; Patel, Hanisha; Ramakrishna, Naren
Abstract: PURPOSE: We evaluated median time-to-distant brain failure (DBF), and salvage-free survival from distant brain failure (DBF-SFS) in melanoma brain metastases (MBM) patients who received stereotactic radiosurgery (SRS) and checkpoint inhibitor treatment. METHODS: An IRB-approved retrospective evaluation of 68 MBM patients with 229 metastases treated with SRS between 11/2008 and 2/2017 with at least one post-SRS brain MRI. Time-to-DBF was the interval between initial SRS to MRI revealing any new brain metastases. DBF-SFS was defined as the interval from initial SRS to MRI revealing brain metastases requiring salvage treatment. Survival analysis was performed using Kaplan-Meier estimates and Cox regression. RESULTS: Overall median time-to-DBF was 4.34 months. Median time-to-DBF for patients who received PD-1 inhibitors (5.43mo), ipilimumab without PD-1 inhibitors (3.95mo), and no immunotherapy (3.30mo) were not significantly different (p=0.28). Median overall survival of non-immunotherapy patients was 3.29 months and all DBF occurred within 4 months in this subgroup. Patients with active extracranial primary disease had significantly worse median time-to-DBF (3.58mo) than those without active primary disease (9.90mo) (HR 3.25, p< 0.01). Overall median DBF-SFS was 4.50 months. Median DBF-SFS for patients who received PD-1 inhibitors (9.21mo), ipilimumab without PD-1 inhibitors (5.44mo), and no immunotherapy (4.50mo) were not significantly different. Multivariate analysis confirmed a significantly worse DBF-SFS for patients with > 2 SRS-treated metastases (2.30mo) versus 1–2 metastases (9.21mo), (HR 10.22, p< 0.01). Patients treated in 2014 or later demonstrated significantly longer DBF-SFS (median not reached) vs those treated prior to 2014 (4.34mo) (HR 0.01, p=0.01). CONCLUSIONS: Our study demonstrated improving DBF-SFS rates for patients treated since 2014 compared to those treated earlier. Our study does find that patients with active extracranial disease and > 2 initial metastases have higher rates of DBF and DBF-SFS.